Safety of Platelet‐Rich Plasma Subepithelial Infusion for Vocal Fold Scar, Sulcus, and Atrophy. (13th July 2022) - van der Woerd, Benjamin; O'Dell, Karla; Castellanos, Carlos X; Bhatt, Neel; Benssousan, Yael; Reddy, Neha K; Blood, Timothy; Chhetri, Dinesh K; Johns, Michael M
Abstract : Objective: To demonstrate the safety profile of platelet‐rich plasma (PRP) as an injectable therapeutic for the treatment of vocal fold scarring and atrophy. Methods: Preliminary report on a prospective clinical trial of patients with vocal fold scar or atrophy undergoing unilateral vocal fold subepithelial infusion with autologous PRP. Enrolled patients underwent four subepithelial injections spaced 1 month apart. Adverse events were assessed peri and post‐injection at each session. Patient‐reported outcomes were collected at every visit using the Voice Handicap Index‐10 (VHI‐10) and Vocal Fatigue Index (VFI) questionnaires. Results: Twelve patients underwent unilateral vocal fold injection with autologous PRP prepared according to Eclipse PRP® system protocol. Forty‐three injections were performed using a peroral or percutaneous approach. An average of 1.57 ± 0.4 cc (range 0.6–2.0 cc) injectate was used. All patients tolerated the procedure without difficulty or peri‐procedural complications. The average duration of follow‐up was 3.6 ± 1.8 months. No significant inflammatory reactions or adverse events were seen to date. There was statistically significant improvement in patient‐reported outcomes at the 3 month follow up ( n = 9) follow‐up (mean ΔVHI‐10 = 10.8, p < 0.001, mean ΔVFI = 18.9, p = 0.01, t test, paired two sample for means, two‐tail). All nine patients who completed the series of four injections subjectively (yes/no) reported they were satisfied with the results. Conclusion: This prospective study cohort demonstrated a favorable safety profile, with no adverse events or peri‐procedural complications. Subjective improvements in vocal quality and reduction in vocal fatigue need to be clinically correlated with further study. Level of Evidence: 4 Laryngoscope, 133:647–653, 2023 Abstract : This prospective study cohort demonstrated a favorable safety profile, with no adverse events or peri‐procedural complications. Subjective improvements in vocal quality and reduction in vocal fatigue need to be clinically correlated with further study.